ANALISIS PERMASALAHAN PENERAPAN MEDIA PEMBELAJARAN BIOLOGI PADA SMA NEGERI 2 BAGAN SINEMBAH DI KELAS XII - Mia Angelia Fatmawati; Odelia Nova Maria Br. Sitohang; Grace Elizabeth Victoria Sitorus; Widya Arwita; Aswarina Nasution (Cahaya Ilmu Bangsa Institute, 2025)
The application of learning media in Biology subjects has an important role in helping students understand complex and abstract concepts. However, in practice, there are still various obstacles that hinder the effectiveness of its use. This study aims to analyze the problems that arise in the application of Biology learning media to grade XII students at SMA Negeri 2 Bagan Sinembah. This study uses a descriptive method with a combination approach. Data were collected by distributing questionnaires to 36 students and interviews with Biology teachers via Zoom Meeting. The results of the study showed that the learning media that students liked the most was audio-visual media because it was able to improve understanding, memory, and involvement in learning. However, obstacles were still found such as limited internet signal, availability of facilities, and teacher skills in making teaching media. This confirms that the effectiveness of learning media is greatly influenced by infrastructure readiness, teacher competence, and student characteristics. Therefore, attention is needed to improve this condition through optimizing educational facilities and training in the use of technology.